The sexually frustrated, the dumb and the libtard traitors: A typology of insults used in the positioning of multiple others in Irish online discourse relating to refugees, asylum seekers, immigrants and migrants - Devlin, Anne Marie; Grant, Ciara (European journal of communication (London), 2017)
Based on the framework devised by Korostelina, the purpose of the study is to explore the typology of insults used in the positioning of multiple others by Irish Facebook users in response to Irish Independent newspaper articles concerning the 2016 refugee crisis in Europe. While the main focus rests on positioning the voiceless refugees, asylum seekers and immigrants, the study also illuminates how those with voices deploy insults to position each other. The study concludes that insults are deployed differentially both quantitatively and qualitatively depending on whether the recipient has a voice. In the online domain, the voiceless are subject to a greater number and range of insults.